Le risque trophique : caractéristiques trophique et hétérogénéité des ressources alimentaires en lien avec les mortalités ostréicoles - Ropert, Michel; Lefebvre, Sebastien; Soletchnik, Patrick; Blin, J. L.; Faury, Nicole; Struski, Caroline (Présentation Séminaire MOREST, Caen, 14-26 novembre 2004, 2004)
The "trophic risk" has been demonstrated in the bioenergetic model developed in vivo and based on various diet conditions similar to those of different types of oyster culture basins (eutrophic, heterotrophic and oligotrophic) [22, 23]. The trophic resource – mortality relationship differs from one basin to another, according to the quantity of this resource. Multy-varied analysis (ACP) conducted on a total of 11 oyster culture sites and handled in a database matching mortality and environmental data, show that the trophic indicator "chlorophyll a" (often coupled with temperature) is involved in a positive correlation with the mortality of both age classes (1 and 2 years old). The stock transfer from the Bay of Veys to the west coast of Cotentin in spring shows that the "avoidance" of the Bay of Veys in spring saves the stocks [24]. An atypical year like 2004 shows that an important trophic resource on the west coast of Cotentin alone is not enough to cause high mortality rates (absence of an "x" factor), but, on the other hand, a low trophic resource in the Bay of Veys in 2004 saves the oysters that have been kept there, despite the probable presence of the "x" factor! As a consequence, the trophic factor is demonstrated in the eutrophic basin of the Bay of Veys. Its presence in the "oligotrophic" Marennes Oléron Bay, where the trophic resource is globally limiting, is less obvious. The changes in the quality of the trophic resource, more organo-detritic in spring, and turning into a more benthic resource at the end of spring and in summer [5]. On a larger scale, multivaried analysis [13] systematically show pheopigments as an indicator which is positively linked to mortality in the case of spring mortality of 2-year-old oysters. This made us think that an excess of pheopigments in spring could affect the survival of the species. The mortality of the 1-year-old oysters could be linked negatively to the large amount of pheopigments in summer, showing that (1) nutritional requirements between 1 and 2 year olds ...